Evaluation of muscle lipid extraction and non‐lethal fin tissue use for carbon, nitrogen, and sulfur isotope analyses in adult salmonids. (21st April 2021) - Larocque, Sarah M.; Fisk, Aaron T.; Johnson, Timothy B.
Abstract : Rationale: Chemical lipid extraction or using alternative tissues such as fish fin as opposed to muscle may alter isotopic ratios and influence interpretations of δ 13 C, δ 15 N, and previously unassessed δ 34 S values in stable isotope analyses (SIA). Our objectives were to determine if lipid extraction alters these isotope ratios in muscle, if lipid normalization models can be used for lipid‐rich salmonids, and if fin isotope ratios are comparable with those of muscle in adult salmonids. Methods: In six adult salmonid species (n = 106) collected from Lake Ontario, we compared three isotope ratios in lipid‐extracted (LE) muscle with bulk muscle, and LE muscle with fin tissue, with paired t‐tests and linear regressions. We compared differences between δ 13 C values in LE and bulk muscle with predicted values from lipid normalization models and the log‐linear model of best fit and determined model efficiency. Results: The δ 15 N values in LE muscle increased (<1‰) relative to bulk muscle for most salmonids, with relationships nearing 1:1. There were either no differences or strong 1:1 relationships in δ 34 S values between species‐specific bulk and LE muscle. One lipid normalization model had greater model efficiency (97%) than the model of best fit (94%). Fin had higher δ 13 C values than LE muscle while δ 15 N trends varied (<1‰); however, both isotope ratios had either no or weak linear relationships with fin and LE muscle within species. The δ 34 S values in fin were similar to those in LE muscle and had strong 1:1 relationships across species. Conclusions: We recommend using the lipid normalization model to adjust for δ 13 C values in lipid‐rich muscle (C:N >3.4). LE muscle could be used without δ 15 N or δ 34 S adjustments, but the minimal increase in δ 15 N values may affect SIA interpretation. With high unexplained variability among adult species in fin‐muscle δ 13 C and δ 15 N relationships, species‐specific fin‐muscle adjustments are warranted. No fin‐muscle tissue adjustment would be required for δ 34 S values.